Implementation of Quality Function Deployment (QFD) to Improve Service Quality at Neat Barbershop in Bandar Lampung - Anggraini, Lilie; Rr. Erlina; Ambarwati, Dwi Asri Siti (Basecamp Economics PubMed, 2024)
Neat Barbershop is a business in the service sector located on Jl. Gajah Mada No. 55 CD, Kota Baru Bandar Lampung which aims to provide the best quality haircut service of consumer choice. However, Neat Barbershop experiences instability in the number of customers who come and tends to decrease every month. This instability can cause lagging and reduce consumer interest in using services. This study aims to identify the services needed by consumers through the voice of the customer, then analyze which services need to be improved or maximized to achieve customer satisfaction. The method used in this research is the Quality Function Deployment (QFD) method which is a tool to change what consumers want into quality characteristics and develop quality planning to get a satisfactory final result with one of the techniques, House Of Quality (HOQ). Through HOQ analysis, the calculation results for each improvement and development priority resulted in 5 unsatisfactory for consumers, 5 attributes of consumer interest, and technical characteristics of the business that need to be improved to optimize the best service quality.